KARAKTERISTIK PENGAYAK GETAR DENGAN SUMBER EKSITASI POROS EKSENTRIK - Bur, M; Nazaruddin, Nazaruddin; Mahyuddin, A. I; Samudra, J (Mesin, 2000)
Vibrating screen is an equipment used to seperate material according to its particle size. It is usually operated in combination with a crusher. A vibrating screen prototype has been developed. This prototype, called as âPengayak Getar Semen Padang Prototipeâ0l